Analisis Program Lapor Pak Berdasarkan Tinjauan Dari Sudut Pandang Pedoman Perilaku Penyiaran Dan Standar Program Siaran (P3SPS) Episode Kiki Saputri Roasting Anies Baswedan Di Trans7 - Muhamad Hardandy Sutrisno; Harmonis Harmonis (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The Lapor Pak program is a variety show that will be broadcast on Trans7 starting from February 22 2021. Carrying the concept of variety comedy, Lapor Pak is packaged through sketches and talk shows with the background of a police station that comedy current criminal cases, as well as local gossip. artist with a delivery method that aims to invite laughter from the audience. The aim of this research is to determine the content of the report sir episode of Kiki Saputri Toasting Anies Baswedan program in terms of broadcasting behavior guidelines and broadcast program standards (P3SPS). This research uses a qualitative approach with descriptive methods and collects data through interviews, observation and documentation. The research results show that in the Lapor Pak program, the Kiki Saputri Roasting Anies Baswedan episode, there are 4 segments. In segment 4 there are 4 scenes that have the potential to violate P3SPS. According to the researchers, the results of the analysis were no problem because the scene was not slanderous, inflammatory, misleading or lying, the sentences uttered by Kiki were in accordance with the data and the nature of the questions was made with the concept of roasting. In analyzing each broadcast, researchers observed the scenes of each segment and each minute of the video, then looked closely at all the scenes in the video. Then, after researchers watched the video, they found no violations listed in accordance with the P3SPS article. This research illustrates how Trans7 succeeded in creating creative programs that did not violate broadcasting regulations.